Stewardship of resources in the South African Public Sector Institutions - Hlongwane, P. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
The purpose of this paper is to assess the extent to which public officials adhere to the basic principles of stewardship in the use and management of public resources in the South African public sector institutions. In this regards, it is imperative to note that public officials have a significant role to fulfil as stewards or managers of financial and non-financial resources entrusted upon them. Moreover, public officials (stewards) are responsible for protecting or safeguarding public resources in an efficient and responsible manner. Despite this pivotal role, public officials misuse resources entrusted to them for personal gain at the expense of general populace. In order to comprehend and appreciate the importance of stewardship in the context of public sector institutions, this paper presents the scope and definition of stewardship. The paper argues that the resources under the custodianship of public officials belong to the citizens and therefore ought to be managed with utmost circumspection. To this end, public officials have to denounce greediness and corruption thereby exercising self-control in order to eschew misuse of scarce resources. Further, this paper maintains that if public officials aspire to abide by basic tenets of stewardship they must be accountable, trustworthy, honest and loyal to the citizens. Building a relationship of trust and maintaining loyalty to the citizens is important primarily because citizens are the real owners of resources under the control of public officials. Equally important, citizens deserve to be treated with positive attitude, humility and care. In other words, stewardship ought to be a manifestation of love for the citizens by public officials. It is also argued that to be good stewards requires total commitment or dedication from public officials in managing resources. This paper concludes that failure by public officials to give account for the utilisation of resources and ineptitude to render quality service to the citizens with humility in the South African public sector institutions constitutes an antithesis of the spirit of stewardship.
Journal article published in the 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Accountability; Discipline; Professionalism; Stewardship; Trust; Government accountability; Public administration; Public institutions